Ledipasvir and sofosbuvir for hepatitis C genotype 4: a proof-of-concept, single-centre, open-label phase 2a cohort study. Issue 9 (September 2015) - Kohli, Anita; Kapoor, Rama; Sims, Zayani; Nelson, Amy; Sidharthan, Sreetha; Lam, Brian; Silk, Rachel; Kotb, Colleen; Gross, Chloe; Teferi, Gebeyehu; Sugarman, Kate; Pang, Phillip S; et al.
Summary Background Worldwide, although predominantly in low-income countries in the Middle East and Africa, up to 13% of hepatitis C virus (HCV) infections are caused by HCV genotype 4. For patients with HCV genotype 1, the combination of ledipasvir and sofosbuvir has been shown to cure high proportions of patients with excellent tolerability, but this regimen has not been assessed for the treatment of HCV genotype 4. We assessed the efficacy, safety, and tolerability of 12 weeks of combination therapy with ledipasvir and sofosbuvir for patients with chronic HCV genotype 4 infections. Methods In this single-centre, open-label cohort, phase 2a trial, patients with HCV genotype 4 who were treatment naive or interferon treatment experienced (HIV-negative) were sequentially enrolled at the Clinical Center of the National Institutes of Health, Bethesda, MD, USA. We gave patients 12 weeks of ledipasvir (90 mg) and sofosbuvir (400 mg) as a single combination tablet once per day. The primary efficacy endpoint was sustained viral response at 12 weeks (SVR12), as measured by the proportion of patients with HCV RNA concentrations less than the lower limit of quantification (COBAS TaqMan HCV test, version 1.0, 43 IU/mL). The primary safety endpoint was the frequency and severity of adverse events. We did our analyses on an intention-to-treat basis. This study is registered with ClinicalTrials.gov, number NCT01805882. Findings Between Sept 16, 2013, and Nov 2, 2014, we recruited 21 patients. 20 (95%) of 21 patients completed 12 weeks of treatment and achieved SVR12 (95% CI 76–100), including seven patients with cirrhosis. One patient was non-adherent to study drugs and withdrew from the study, but was included in the intention-to-treat analysis. No patients discontinued treatment because of adverse events and no grade 3 or 4 adverse events occurred that were related to study medications. The most common adverse events were diarrhoea (two patients), fatigue (three patients), nausea (two patients), and upper respiratory infections (two patients). Interpretation Ledipasvir and sofosbuvir treatment for 12 weeks was well tolerated by patients with HCV genotype 4 and resulted in 100% SVR for all patients who received all 12 weeks of study drugs, irrespective of previous treatment status and underlying liver fibrosis. This is the first report of a single-pill, all-oral, interferon-free, ribavirin-free treatment for patients with HCV genotype 4. Funding NIAID, National Cancer Institute and Clinical Center Intramural Program. The study was also supported in part by a Cooperative Research and Development Agreement between NIH and Gilead Sciences.